STUDY ON CONSTRUCTION PROJECTS INDIRECT COST ESTIMATING PRACTICES BY ON LARGE CONTRACTORS IN JAKARTA AND BANDUNG - YUSUF (NIM : 250 08 014); Dosen Pembimbing, Ir. Biemo W. Soemardi, MSE., Ph.D., DIANA
Indirect cost is part of the of construction project costs that cannot associated directly with the physical component of the end volume of the project, but have contributed to the completion of the project. Indirect cost estimation is not easy to do compared to estimating the direct costs, which can easily refer to the drawings and technical specifications. Common practices by contractor in Indonesia in determining indirect cost is by setting the amount of indirect costs as a percentage of direct costs based on previous project experience. This study examined the practices by major contractors in estimating indirect costs in order to obtain a picture of the pattern characteristics indirect cost estimation and make a model with regression analysis to obtain the weight of the big picture indirect costs in a construction project. The data used in this study was gathered by survey in the form of interviews and data collection costs to the company's major qualifying contractors. The survey was conducted to a large contractor 35 respondents consisting of 15 large contactors in Jakarta and 20 major contractors in Bandung and the model cost estimates based on information analyzed data on supply costs. The results showed that the estimated indirect costs should be able to anticipate uncertainty of the risk cost. The pattern characteristics indirect cost estimates is obtained by identifying the characteristics of the project and then describe indirect cost components and determine the proportion of value into the percentage of indirect expenses. In another part this study also modeled the indirect cost estimation based on project cost data. The model showed nonlinear relationship between ratio of indirect cost to total project value and the total project value. The model indicates that the greater the contract value the smaller the ratio of the indirect cost become.